2018
DOI: 10.3390/nano8110934
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Reduced Graphene Oxide/Titanium Dioxide Nanotubes (rGO/TNT) Composites as an Electrical Double Layer Capacitor

Abstract: Composites of synthesized reduced graphene oxide (rGO) and titanium dioxide nanotubes (TNTs) were examined and combined at different mass proportions (3:1, 1:1, and 1:3) to develop an electrochemical double layer capacitor (EDLC) nanocomposite. Three different combination methods of synthesis—(1) TNT introduction during GO reduction, (2) rGO introduction during TNT formation, and (3) TNT introduction in rGO sheets using a microwave reactor—were used to produce nanocomposites. Among the three methods, method 3 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(22 citation statements)
references
References 23 publications
0
22
0
Order By: Relevance
“…6, a, all the CVA curves measured for rGO electrodes exhibit almost close to rectangular shapes in the range of 0 V to 0.5 V that is the evidence of a reversible capacitive behaviour of charge accumulation. The transformation of CVA curves with scan rate increasing is typical for EDL charge accumulation type [15]. The pair of well-defined redox peaks is observed on CVA plots of Ni(OH) 2 -based electrode (Fig.…”
Section: Resultsmentioning
confidence: 78%
“…6, a, all the CVA curves measured for rGO electrodes exhibit almost close to rectangular shapes in the range of 0 V to 0.5 V that is the evidence of a reversible capacitive behaviour of charge accumulation. The transformation of CVA curves with scan rate increasing is typical for EDL charge accumulation type [15]. The pair of well-defined redox peaks is observed on CVA plots of Ni(OH) 2 -based electrode (Fig.…”
Section: Resultsmentioning
confidence: 78%
“…The XRD of rGO had a sharp peak presence at 25.2°, 43.8°, and 45.6° as shown in Figure 9 a. These peaks correspond to (002), (001), and (001) diffraction planes while the 25.2° peak indicated that the reduction process from graphene oxide (GO) was successfully obtained [ 41 , 42 ]. Moreover, less intense peaks at 43.8° and 45.6° indicated highly disordered carbon material [ 32 ].…”
Section: Resultsmentioning
confidence: 99%
“…59 The mass ratio of N-doped graphene : TiO x N y is approximately 2 : 1, which results in a signicant decrease of specic area and electrochemical active area as opposed to sole N-doped graphene and a further decrease of specic capacitance. 46,60,61 Fig. 5c shows the I-V curves for electrolyte solutions with concentrations of 0.1 mol L À1 , 0.5 mol L À1 , and 1 mol L À1 .…”
Section: Resultsmentioning
confidence: 99%